2013
DOI: 10.20533/ijels.2046.4568.2013.0029
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Theories and Models for Studying the Integrating Physical and Virtual Identity Access Management Systems

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These findings are in agreement with Malima et al (2015) who argue that PE is found to uniquely, significantly and positively influence one's behavioural intension to accept and use mobile technologies in agricultural marketing. Alotaibi et al (2013) also argued that once the strength of a behavioural intention to conduct an act is greater, then it is more likely that such an act will be conducted in the future.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with Malima et al (2015) who argue that PE is found to uniquely, significantly and positively influence one's behavioural intension to accept and use mobile technologies in agricultural marketing. Alotaibi et al (2013) also argued that once the strength of a behavioural intention to conduct an act is greater, then it is more likely that such an act will be conducted in the future.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Behavioural intention to use is referred to as an individual's decision to exhibit a particular behaviour in the future. It is also argued that once the strength of a behavioural intention to conduct an act is greater, then it is more likely that such an act will be conducted in the future (Alotaibi et al, 2013). Several studies conducted (Malima et al 2015;O'Neill, 2010) have JSIT 18,4…”
Section: Relationship Between Performance Expectancy and Behavioural Intention To Use Pe Has Been Defined Bymentioning
confidence: 99%
“…Research has explored ways of predicting the use of a new system based on individual intentions and how one's attitude might contribute to those intentions (Alotaibi & Wald, 2013). Technology implementation and the associated changes have been the focus of a great deal of research, with a significant foundation in the Theory of Reasoned Action (TRA) first presented by Fishbein and Ajzen.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the above frameworks have been analysed in the previous papers [12], [26], which summarises a…”
Section: Comparing Existing Frameworkmentioning
confidence: 99%
“…Two factor authentication [1] a Nounce-based authentication [1] b User Anonymity [1] c Control of information [7][8] d Conceal Information [7][8] e Security Certificates [9][10] f WS Federation Specification [9][10] g Acceptability Incremental Learning [11][12][13][14] h Linearity [11][12][13][14] i Scaffolding [11][12][13][14] j Learning Control [11][12][13][14] k Accommodating to the learner's style [11][12][13][14] l Intermittent feedback [11][12][13][14] m…”
Section: Attributes Label Securitymentioning
confidence: 99%